Assessment of Serratia sp. isolated from iron ore mine in hexavalent chromium reduction: kinetics, fate and variation in cellular morphology. Issue 9 (15th April 2020) - Upadhyay, Shivangi; Tarafdar, Abhrajyoti; Sinha, Alok
ABSTRACT: Serratia sp. strain SU.ISM.1 was isolated from Noamundi iron ore mines for the first time and was observed for hexavalent chromium reduction, and growth kinetics modelling was applied for bacterial chromium reduction. For 4–8 ppm of hexavalent chromium concentration, complete reduction was observed within 36 h when the selected isolate was applied, and for 12–20 ppm chromium concentration, complete reduction was achieved within 48 h. The viable biomass concentration increased up to 36 h of treatment time, after which the biomass concentration gradually declined. The Aiba model of product inhibition growth kinetics best described the growth of biomass in the presence of hexavalent chromium. The total mass conversion of Cr(VI) to Cr(III) for 4, 8, 12, 16 and 20 ppm was found to be 94.9%, 88.5%, 74.66%, 70.75% and 78.8%, respectively. The AFM and FESEM studies showed that the roughness of the cell surface increased with increasing concentration of hexavalent chromium, probably due to adsorption of chromium. GRAPHICAL ABSTRACT: